Targeting the Poorest in Microfinance: Poverty outreach of BDP ultra poor program - Barua, Proloy; Sulaiman, Munshi (BRAC Research and Evaluation Division and Aga Khan Foundation Canada, 2022)
Despite the general consensus that microfinance does not reach the poorest; recent evidence suggests that nearly 15% of microfinance clients in Bangladesh are among the poorest. It is from the realization that even within the existing microfinance membership of BRAC, there is a significant percentage of the poorest; the CFPR-TUP program has included a special focus on this segment of the poor what it calls the ‘BDP ultra-poor’. So, BDP ultra-poor people are those struggling members of existing Village Organization (VO) or very poor households in a village who with some additional support can more fully participate and benefit from microfinance services. This study attempts to assess the targeting effectiveness of the BDP ultra-poor program by measuring the relative poverty of BDP ultra-poor. A total of 1,339 households were surveyed from 30 area offices consisting of BDP ultra-poor, VO members and non-VO members. Findings show that 46% of BDP ultra-poor households belong to the poorest quartile and most of the remaining BDP ultra-poor households belong to moderate poor quartile that suggests the program is being able to concentrate on the target population. It was also found that the current focus on BDP ultra-poor targeting is on the poorer VO members since the majority of BDP ultra-poor households was selected from existing BRAC microfinance VOs. To improve targeting effectiveness of BDP ultra-poor package further, the focus will have to be on the poorest households outside the VOs most of whom have never participated in any microfinance programs and possessed extremely low poverty score.